Space Debris: A Robotic Mission to Clean the Earth's Orbit - Nizza, Tomás; Pereyra, Agustín; Reinante, Lautaro (Inglés II. Universidad Tecnológica Nacional. Facultad Regional Paraná, 2025)
Abstract— In recent decades, the accumulation of space debris has become a growing concern for the scientific and aerospace communities. Since the beginning of the space era in 1957, rockets, spaceships and satellites have been launched into space. However, the issue of what to do with them at the end of their useful life has not been thoroughly discussed. To address this issue, the United Nations’ Sustainable Development Goal (SDG) #12, “responsible production and consumption”, aims to ensure sustainable consumption and production patterns and to cut all waste by 2030, yet with five years to go, there still are many decisions to make. This target is closely related to the problem addressed in this paper since, according to studies carried out at the end of 2017, there are 8,135 tons in Earth's orbit, making it necessary to analyze solutions to deal with the waste produced by space activities. Bearing SDG #12 in mind, the proposed solution is to detect and collect pieces of space debris using a spacecraft with four robotic arms. Thus, this paper analyzes this robotic mission to solve the problem that continues to grow day. It aims to study the effects of space debris on the Earth's atmosphere and the planet’s longevity, as well as to provide an overview of the proposed solution. Furthermore, it describes the evolution of the debris problem, its impact on future missions, and the proposed detection and collection methods, seeking to raise awareness and inspire collaboration on sustainable technological solutions.

Resumen— En las últimas décadas, la acumulación de desechos espaciales se ha convertido en una preocupación para las comunidades científicas y aeroespaciales. Desde el comienzo de la era espacial en 1957, se han lanzado cohetes, naves espaciales y satélites. Sin embargo, la cuestión de qué hacer con ellos al final de su vida útil no ha sido discutida a fondo. Para abordar este problema, el Objetivo de Desarrollo Sostenible (ODS) #12 de las Naciones Unidas, “producción y consumo responsables”, tiene como meta garantizar patrones sostenibles de consumo y producción y eliminar los desechos para 2030, sin embargo, con cinco años por delante, aún quedan muchas decisiones por tomar. Este objetivo está estrechamente relacionado con el problema tratado en este trabajo, ya que, según estudios del 2017, existen 8.135 toneladas en la órbita terrestre, lo que hace necesario analizar soluciones para tratar los residuos generados por las actividades espaciales. Teniendo en cuenta el ODS #12, la solución propuesta es detectar y recolectar piezas de desechos espaciales utilizando una nave espacial con cuatro brazos robóticos. Así, este trabajo analiza esta misión robótica para resolver el problema que continúa creciendo. Su objetivo es estudiar los efectos de los desechos espaciales en la atmósfera terrestre y la longevidad del planeta, así como ofrecer una visión general de la solución propuesta. Además, describe la evolución del problema de los desechos, su impacto en las misiones futuras y los métodos propuestos de detección y recolección, buscando generar conciencia e inspirar la colaboración en soluciones tecnológicas sostenibles.
Keywords: Inglés II; Space debris; Earth orbit; Basura espacial; Órbita terrestre